Nest-departure behaviour of gynes and drones in the invasive yellowjacket Vespula germanica (Hymenoptera: Vespidae) - Martinez Von Ellrichshausen, Andres Santiago (2020)
Inbreeding costs can be high in haplodiploid hymenopterans due to their particular mechanism of sex determination (i.e., single-locus complementary sex-determination system, sl-CSD), as it can lead to the production of sterile males. Therefore, mechanisms contributing to reduced inbred matings can be beneficial. In this sense, asynchronous nest departure of sibling drones and gynes could reduce kin encounters in social hymenopterans. Using six observation colonies, we determined under field conditions the nest departure behaviour of sibling reproductives of the social wasp Vespula germanica (Hymenoptera: Vespidae). We determined that sexuals leave the nests definitively and detected asynchronous departure not fixed to a particular caste at a seasonal scale in some colonies, as gynes or drones delayed their departure as a function of the departure of the opposite sex, depending on the colony. At a higher temporal resolution (i.e., within a day), we discovered that drones consistently began to leave nests 1 h before gynes and this difference was driven by those individuals that left on the same day as did the opposite-sex kin. Even though other mechanisms such as polyandry and differential dispersal could also be important at reducing inbred matings in the species, the observed departure patterns (i.e., in some colonies actually leave together with the opposite caste, while in others temporal segregation seems to occur) from nests could be complementary to the former and be important at reducing the negative effects of inbreeding in this invasive species.